2016
DOI: 10.1590/1807-3107bor-2016.vol30.0069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alpha-tocopherol on fracture resistance after endodontic treatment, bleaching and restoration

Abstract: This study evaluated the effects of 10% alphatocopherol on the fracture resistance of endodontically treated teeth subjected to tooth bleaching with hydrogen peroxide and immediately restored with composite resin. Fifty bovine incisors were selected, including 10 sound teeth that constituted the control group (G1 (C)). The remaining 40 teeth, which were endodontically treated, were divided into four groups (n = 10): G2 (CR), consisting of teeth immediately restored with composite resin; G3 (HP + CR), consistin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 32 publications
2
20
1
2
Order By: Relevance
“…The PDT/CC group presented lower dentinal penetrability in the cervical and apical thirds. It can be associated with the high concentration of oxygen, which worked as a mechanical barrier and hampered the penetration of the adhesive system in the dentinal tubules (10). Moreover, Grandini et al (24) have observed that higher incidences of gaps and cementation failures occurred in the apical third of the prosthetic space, similar to the specimens in the PDT/CC group, because of the presence of oxygen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PDT/CC group presented lower dentinal penetrability in the cervical and apical thirds. It can be associated with the high concentration of oxygen, which worked as a mechanical barrier and hampered the penetration of the adhesive system in the dentinal tubules (10). Moreover, Grandini et al (24) have observed that higher incidences of gaps and cementation failures occurred in the apical third of the prosthetic space, similar to the specimens in the PDT/CC group, because of the presence of oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the degree of conversion and the adhesion of resinous materials to the dentin are compromised by the substances that interact with these free radicals, such as sodium hypochlorite, which degrades in sodium hydroxide and hypochlorous acid and, consequently, leads to singlet oxygen formation (7)(8)(9). Moreover, the presence of oxygen can also work as a barrier in the adhesive interface, which hampers hybrid layer formation in dentin (10).…”
mentioning
confidence: 99%
“…Next, a size 15 K-file (Dentsply Maillefer) was inserted, and the canals were prepared according to a stepback technique up to a size 60 K-file. The canals were irrigated with 1 mL of 1.0 % NaOCl at each change of the file during chemomechanical preparation and then filled with 2 mL of 17 % EDTA for 3 min, flushed with 2 mL of 1 % NaOCl and dried with absorbent paper points (Dentsply Maillefer) [26].…”
Section: Initial Proceduresmentioning
confidence: 99%
“…1,2 Hydrogen peroxide is a strong oxidizing agent, which produces free radicals, reactive oxygen molecules, and HP anions that act on the pigments converting them into small molecules with reduced light absorption and low molecular weight, easier to be removed from the dental structure. 3,4 To improve the physical and chemical properties of HP, various components have been added to the bleaching gel, such as thickeners, desensitizers, remineralizers, and pigments. 5,6 Pigments facilitate the gel visualization and accelerate the chemical reaction that triggers tooth bleaching due to the bleaching gel having greater light absorption properties.…”
Section: Introductionmentioning
confidence: 99%